Fratura cominutiva e articular distal de úmero tratada com fixador esquelético externo transarticular em três gatos - Dal-Bó, Ísis dos Santos; Ferrigno, Cássio Ricardo Auada; Macedo, Aline Schafrum; Ferreira, Márcio Poletto; Marinho, Paulo Vinícius Tertuliano; Paes, Fernanda; Bregadioli, Thales; Monteiro, Bianca Fiuza (Acta Scientiae Veterinariae, 2017)
Background: Humeral fractures account for 13% of all fractures in cats and commonly affect the middle diaphysis and supracondylar region with comminution. They are usually the result of high energy traumas such as falls, car accidents and firearm injuries. There are few treatment options for these types of fractures and since they are joint injuries, early surgical repair is mandatory to achieve perfect anatomical reduction, to maintain joint congruence and to allow early weight bearing. Our purpose is to report four subacute and chronic fractures of the distal diaphysis associated with comminuted supra and intercondylar fractures, stabilized with transarticular external skeletal fixator in three domestic felines. Cases: (1)- A 3-year-old male docile Siamese cat with 3.7 kg of body weight was presented for consultation with a 14-day history of high rise syndrome after falling from a 12-meter high. It presented distal comminuted humeral fracture that involved the inter and supracondylar regions. It also had right carpal-ulnar subluxation and comminuted right olecranon fracture involving the articular surface in the left thoracic limb. Fracture and joint stabilization was achieved by use of a transarticular hybrid external skeletal fixator on the right front limb. Fracture healing was observed at 150 days postoperatively. (2)- A 10-year-old female aggressive mixed breed cat with 4.1 kg of body weight was presented for consultation with a 16-day history of high rise syndrome after falling from a 9-meter high. The cat had a comminuted right humeral articular fracture with supra and intercondylar involvement and scapular fracture on the contralateral limb. The humerus fracture was treated with a transarticular linear external skeletal fixator and fracture healing was obtained at 240 postoperative days. (3)- A 1-year-old female unsociable mixed breed cat with 4.5 kg of body weight was presented for consultation with a 15-day history of humeral fractures after falling from a 12-meter high building. The cat had comminuted bilateral humeral articular fracture with supra and intercondylar involvement. Fracture stabilization was achieved by use of a transarticular hybrid external skeletal fixator on both limbs. Fracture healing was achieved after 60 days on the right front limb, and after 120 days on the left front limb. Discussion: Patients with distal humeral diaphyseal fractures should be assessed for peripheral nerve injury. None of the reported cases had neurological damage despite having suffered high energy trauma. Surgical approach to humeral distal fractures may be craniolateral, medial or caudal or even combined. In chronic fractures like those in our study, (fractures with more than 14 days of evolution), perfect anatomic reduction wasn’t considered due to presence of fibrous tissue that would require excessive manipulation, leading to injuries to soft tissues and blood supply, what would increase the risk of infection and bone sequestrum. The gold standard for the treatment of articular fractures is rigid internal fixation by means of compressive screws and compressive plates, and they require open reduction. Whenever anatomical reduction can not be performed, due to either the fracture’s evolution period or by the diminished bone length, closed reduction is indicated and stabilization with transarticular fixators is an alternative. Hybrid constructs are well tolerated by patients since they are lighter than circular apparatus and more versatile than linear fixators. In our study, transarticular fixators were used based on the location of the fractures and fracture period. Despite the ankyloses of the humeral-radio-ulnar joint, all patients adapted to the fixator devices very well and presented satisfactory ambulation weight bearing on the first postoperative day already. A disadvantage of the skeletal fixators is the postoperative care, which includes daily dressings, e-collaring, resting and co-operation on behalf of the owner. Two animals presented aggressive/unsocial behavior and still the prolonged postoperative management and adaptation to the fixator were successful. The results suggest that comminuted humeral distal articular fractures can be treated by the use of transarticular external skeletal fixators in cats.